Implications of a twelve-week aerobic exercise on functional work capacity in HIV positive clients on antiretroviral therapy - Mwebaze, Nicholas; Nsibambi, Constance A. N.; Ojuka, Edward; Maghanga, Mshilla (Turkish Journal of Kinesiology, 2024)
The implications of aerobic exercise on functional work capacity of Human Immunodeficiency Virus (HIV) positive clients on antiretroviral therapy (ART) in Uganda have been established. ART and the efforts to scale it up have significantly improved the value of life and life’s hope of among PLHIV. Despite the presence of ART HIV disease is still seen in wards and a significant loss of life due to AIDS. This study provides useful information to the Ministry of Health of Uganda on the implications of aerobic exercises on functional work capacity as a clinical outcome to HIV positive clients in Uganda. This helps in refining the existing information on aerobic exercises and their relevancy in management of HIV positive clients. An experimental study was conducted among HIV positive clients who had been on treatment for at least 12 months prior to the study. Volunteers were randomly assigned to a control group (Group 1), where no treatment was administered, and an experimental group (Group 2), where a twelve-week moderate intensity aerobic exercise was administered. Assessment of functional work capacity was done as a pre-test and post-test for both groups. The results showed that aerobic exercises significantly improved both heart rate and VO2max with p-values of <0.001 indicating a significant improvement of VO2max from 25.13 to 34.19ml/kg/min while the control group improved by 3.73ml/kg/min. Aerobic exercise can, therefore, improve the quality of life; reduce the cost of management, mobility and mortality rates in HIV positive clients on ART in Uganda.